BRAZILIAN INNOVATION TAX POLICY AND INTERNATIONAL INVESTMENT: EVIDENCE FROM UNITED STATES MULTINATIONALS AND INTERNATIONAL PATENT APPLICATIONS - Colombo, Daniel Gama e (Análise Econômica, 2019)
In the last decades, multinational enterprises (MNEs) have increased their internationalization levels of innovation activities. Brazil has benefited from such changes and received increasing investment from MNEs. In 2005, the federal government approved new tax incentives (Law 11,196/05) to foster business innovation in the country by reducing the tax cost of research and development (R&D) activities. This paper investigates whether these tax breaks have attracted ‘footloose R&D’, diverting international investment from other economies. After a literature review on locational factors for R&D attraction and an analysis of the Brazilian case, an econometric model is presented, using data on R&D investment by U.S. MNEs and priority patent applications. No evidence that Brazilian tax incentives have attracted international R&D from alternative host countries is found. This result is in accordance with previous research suggesting international R&D performed in Brazil is mainly adaptive and support-oriented and, for this reason, tax incentives are not a primary attraction factor. It also suggests that claims that international fiscal competition lead to a zero-sum game may be unfounded for the Brazilian case.